Analisis Tingkat Pencemaran Air Sungai Krueng Tamiang Terhadap COD, BOD dan TSS - Bahagia Bahagia; Suhendrayatna Suhendrayatna; Zulkifli Ak (Fakultas Teknik, 2020)
Industrial waste is a factor influencing the pollution of the Krueng Tamiang river. The purpose of this study was to analyze the level of water pollution in the Krueng Tamiang river with the parameters of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total suspended Solid (TSS) parameters. The results showed the highest BOD parameter test results came from location 2 (Seumadam Bridge) of 3.63 mg / L at stage IV and the lowest BOD value at locations 1 and 6 (Kaloy Village and Alur Manis Bridge) at stage I of 2 mg / L. The highest COD parameter test results came from location 5 (Kota Lintang Bridge) of 21.0 mg / L at stage III and the lowest COD value at location location 1 (Kaloy Village) at stage III, points 1, 3 and 6 (Kaloy Village, Kebon Tengah Suspension Bridge and Alur Manis Bridge) at stage IV of 17.0 mg / L. The highest TSS parameter test results came from location 7 (Peukan Seuruway), namely 295 mg / L phase I in the dry season, and the lowest TSS value at location 1 (Kaloy Village), which was 11 mg / L in stage III during the rainy season.